MENGUNGKAP UNSUR AIR DALAM SEJARAH KOTA MALANG: PENGELOLAAN ASENERING, DAN GORONG-GORONG KOTA 1914-1940 - Hudiyanto, Reza (Jurnal Sejarah dan Budaya, 2010)
Abstract : The management of drainage system in Malang (1920-1935) was problematic. Culture and population density factors influenced the succeed of water management. How people treated drainage equipment was cultural problem. The increasing of population created water pollution. Developing of drainage system reflected racial discrimination, too. Government did not pay attention for problematic drainage system at local population dwelling. Government would concern if the drainage system in local population dwelling was connected to Europe dwelling.